(untitled) (REMUNOM, 2025)
The use of play in the inclusion of autistic children represents one of the most important activities, as it encourages playing, gaming, and creating, promoting cognitive and socio-emotional development and becoming a positive tool for acquiring knowledge. It enhances learning practices through both playful activities and games that stimulate attention, concentration, interest, and communication. The adaptation of materials plays an essential role in this process, as it makes it possible to adjust activities to the specific needs of each autistic child, ensuring active participation in the proposed experiences while respecting sensory, cognitive, and motor particularities. By modifying colors, textures, sizes, or rules, the professional enables play to become accessible and therapeutic. Objective: To analyze the importance of adapting playful activities in order to foster the development of multiple skills and sensory-perceptual improvement in an inclusive context. Methodology: This is a qualitative study using a participant-observation approach, conducted in a clinical setting. Results: It was identified that the use of adapted playful activities and materials significantly contributed to the children’s overall development; the interventions proved effective in expanding communication, shared attention, and emotional expression. Improvements were also observed in social interaction, engagement in proposed activities, and the ability to concentrate during sessions, fostering creativity and making the therapeutic environment more welcoming, inclusive, and enjoyable. Conclusion: When inserted in a planned and intentional manner, the adaptation of materials allows the inclusion process to occur naturally and playfully, respecting each child’s pace, needs, and particularities. Adapted play promotes the development of cognitive and social skills, stimulates creativity, autonomy, self-confidence, and holistic growth through effective inclusion in educational and therapeutic environments.